A Case Study of Indonesian Interference Towards English in Student Essays in The Writing Class - Imam Basuki (ELLITE, 2022)
Contacts of two different languages often lead to some grammatical errors, especially if the source language and target language are from different language families. This study deals with the interference of Indonesian to English found in student essays in the Writing class. The purpose of this study is to uncover cases of language interference carried out by students. The research data is in the form of sentences containing grammatical errors caused by Indonesian interference to English. Data were collected from 35 essays written by students participating in The Writing Course 03 (Class A) from August – December 2021 in the English Literature Department - Faculty of Humanities - Jember University. Once collected, the data are classified and analyzed using an error analysis framework and a sociolinguistic perspective. The results show that there are nine types of grammatical interference which comprise: plural noun forms, the conformity of the subject-verb form, tenses, word forms, prepositions, article, conjunctions,  word pairs        (mismatch), passive form. These grammatical errors prove the interference of Indonesian to English because students are still very strongly influenced by the rules of their native language (Indonesian) when they write essays in English.